Liquid dynamics: challenges for sustainability in the water domain1. (14th June 2014) - Mehta, Lyla; Movik, Synne
<x xml:space="preserve">Abstract</x> Water is essential for human well‐being and is a basic asset for productive livelihoods in many developing countries. It is also key to realizing most of the Millennium Development Goals (MDGs). Although the water MDG was met in 2010, 768 million people around the globe still lack access to safe and adequate water. Huge disparities continue to exist in access between rural and urban areas and rich and poor, as well as inherent social and gender inequalities. We argue that debates about access have so far paid insufficient attention to the long‐term sustainability of systems and services for accessing water. They have also neglected issues concerning uncertainty and social, environmental, and technological dynamics—particularly through addressing power imbalances and enhancing equity. There are two main reasons for this. One, discourses on access tend to be globalized and general, often disconnected from people's lived realities. Two, the dynamic interaction among social, technical, and ecological/hydrological dimensions of water across multiple scales is not adequately taken account of. There is a variety of different pathways in which water systems of access might develop. There are also multiple understandings and framings of water, and the gathering of knowledge about such diverse understandings implies that appraisal of access needs to broaden up to include a wider range of perspectives to inform policy and political discourse. We thus introduce the concept of 'Liquid Dynamics' to capture an understanding of sustainability that takes on board issues of uncertainty, complexity, local knowledge, equity, gender, and power relations. WIREs Water 2014, 1:369–384. doi: 10.1002/wat2.1031 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.